External cephalic version as an opportunity to reduce the percentage of elective caesarean sections - Jadwiga Surówka; Marek Klimek (Termedia Publishing House, 2023)
Non-cephalic foetal positions account for about 3-4% of all timed deliveries. According to the recommendations of the Polish Socie-ty of Gynaecologists and Obstetricians on caesarean section, in the case of a non-cephalic position of the foetus in a singleton preg-nancy, the pregnant woman should be offered external cephalic version (ECV). ECV aims to achieve the head position of the foetus, using manual rotation performed through the abdominal shell, under constant ultrasound guidance. Before the procedure is per-formed, the pregnant woman undergoes the appropriate qualification, and factors that can affect the success or failure of the ECV attempt are analysed. As the literature indicates, to date, not all factors predisposing to the success or failure of the procedure have been recognised and unequivocally confirmed. Successful rotation and achievement of the foetal head position give pregnant women a chance to undergo vaginal delivery, potentially influencing a lower rate of elective caesarean sections.